2001
DOI: 10.1046/j.1439-0507.2001.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and subtyping of Trichophyton mentagrophytes by random amplified polymorphic DNA

Abstract: Trichophyton mentagrophytes is one of the most common pathogens for human and animal dermatophytoses and known as a complex species with variable morphology, and ecologic and genetic backgrounds. We performed random amplified polymorphic DNA (RAPD) analysis on 43 human and 18 animal isolates of T. mentagrophytes along with other 10 anamorphic species of dermatophytes and three teleomorphic species of T. mentagrophytes. Using RAPD analysis with primer 5'-ATGGATC(G,C)(G,C)C-3' (ATGS), all T. mentagrophytes strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Recent studies undertaken by Michel Monod and Yvonne Gräser's groups suggest that the zoophilic strains in T. interdigitale are associated, at least in European veterinary practices, with cats [68], and that a genotypic discrimination using ITS may be possible [unpublished data]. Other animal hosts that have regularly yielded zoophilic T. interdigitale (usually listed as A. vanbreuseghemii) well confirmed by competent mating studies and/or by molecular techniques include rats [69,70], mice [71] chinchilla [71,72], hamsters [70,72,73], dogs [70,74,75], sea lions [70,73], guinea pigs [69], rabbits [75] and squirrels [73]. Phenotypically, the zoophilic T. interdigitale strains corresponding to the old variety 'T.…”
Section: The Arthroderma Vanbreuseghemii Complexmentioning
confidence: 99%
“…Recent studies undertaken by Michel Monod and Yvonne Gräser's groups suggest that the zoophilic strains in T. interdigitale are associated, at least in European veterinary practices, with cats [68], and that a genotypic discrimination using ITS may be possible [unpublished data]. Other animal hosts that have regularly yielded zoophilic T. interdigitale (usually listed as A. vanbreuseghemii) well confirmed by competent mating studies and/or by molecular techniques include rats [69,70], mice [71] chinchilla [71,72], hamsters [70,72,73], dogs [70,74,75], sea lions [70,73], guinea pigs [69], rabbits [75] and squirrels [73]. Phenotypically, the zoophilic T. interdigitale strains corresponding to the old variety 'T.…”
Section: The Arthroderma Vanbreuseghemii Complexmentioning
confidence: 99%
“…It is also important to observe that the results of RAPD-PCR came in complete harmony with the conventional methods employed for identification and characterization of these fungal species. RAPD and ISSR-PCR methods have frequently been used for phylogenetic analysis and identification of dermatophytes (Kim et al, 1999(Kim et al, , 2001Cano et al, 2005;Leibner-Ciszak et al, 2010). Spesso et al (2013) demonstrated that the detection of intra-species polymorphisms in isolates of M. canis by RAPD-PCR may be applied in future molecular epidemiological studies in order to identify endemic strains, the route of infection in an outbreak and the coexistence of different strains in a single infection.…”
Section: T Mentagrophytes (E)mentioning
confidence: 99%
“…However, outside factors such as temperature variation, medium and chemotherapy, can greatly influence the phenotypic characteristic and consequently can make the identification more difficult (Weitzman and Summerbell, 1995;Faggi et al, 2001;Kanbe, 2008;De Baere et al, 2010). Recently, molecular marker approaches, such as nested-polymerase chain reaction (PCR) (Verrier et al, 2013), random amplified polymorphic DNA (RAPD)-PCR (Kim et al, 2001;Baeza et al, 2006;Leibner-Ciszak et al, 2010;Dobrowolska et al, 2011;Spesso et al, 2013), inter-simple sequence repeat (ISSR)-PCR (Cano et al, 2005;Khosrav et al, 2012), PCR-restriction fragment length polymorphism (RFLP) (Yang et al, 2008;RezaeiMatehkolaei et al, 2012;Samuel et al, 2013), real time PCR (Bergmans et al, 2010) and multiplex PCR assay (Arabatzis et al, 2007;Kim et al, 2011) and others have been adapted for detection of dermatophytes from clinical specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular tools, such as RFLP, random amplification of polymorphic DNA and other DNA fingerprinting methods, have also been employed for the identification of selected dermatophytes (e.g. [12,[17][18][19]), but these approaches yield and utilize phenetic (rather than genetic) characters for identification. Various studies [13,[20][21][22][23][24] have identified the first and second internal transcribed spacers (ITS-1 and ITS-2, respectively) of nuclear ribosomal DNA as well as the chitin synthase (chs-1) gene as promising markers for selected species of Trichophyton and Microsporum.…”
Section: Introductionmentioning
confidence: 99%